The Diagnostic Significance of the Holter Monitoring in the Evaluation of Palpitation - Badri Paudel (Journal of Clinical and Diagnostic Research, 2013)
Purpose: To determine the diagnostic yield of the 24-hour Holter monitoring in the patients who were evaluated for palpitations. Methods: A prospective, single-centre study was performed to evaluate the diagnostic yield of the Holter monitoring. The inclusion criteria was age greater then 18 years with the symptom of unexplained recurrent palpitations. The exclusion criteria was patients with known medical causes of palpitation, a history of documented arrhythmias, or a history of or the current use of anti-arrhythmic drugs. The outcomes included a diagnostic Holter monitor recording. Results: The data analysis of the 335 patients who were studied, showed that there were 160 (47.8%) females and 175 (52.2%) males with a mean age of 55± 18.85 years (18 to 90 years). Ventricular ectopics as bigeminy in 36.7% patients and as couplets in 20% patients, were detected. Non-sustained VT was detected in 5.7% patients, VT was detected in 0.9% cases and SVT was detected in 12.5% cases. 3.58% cases had paraxosymal atrial flutter/fibrillation. The ST segment shift which is suggestive of silent ischaemia, was present in 17.6% of the study population. Second or higher degrees of AV blocks were noted in 2 cases, while one patient had the WPW syndrome. Ventricular bigeminy, couplets, VT,SVT and AF were statistically significant in the patients who were over the age of 50 years as compared to those who were less than 50 years. Conclusion: In patients with non-specific symptoms, Holter monitoring has a significant role in the primary diagnosis of myocardial ischaemia or arrhythmia as a cause of such symptoms in the older age groups.